(untitled) (Tạp chí Y học Cộng đồng, 2026)
Background: Dengue fever epidemics occur very complicatedly in annual cycles, the number of cases tends to increase, improving knowledge of disease prevention practices for students is very important, especially first-year students. Objectives: 1) Describe practical knowledge of dengue prevention among first-year students at Bach Mai Medical College in 2024; 2) Identify some factors related to knowledge and practice of dengue fever prevention of the research subjects. Materials and method: Cross-sectional descriptive study, conducted on 315 first-year students using the convenience sampling method from December 2023 to July 2024 at Bach Mai Medical College. Results: Through a survey of 315 first-year students, 18.73% of students had satisfactory knowledge of dengue fever prevention and 45.08% of students had satisfactory practice in dengue fever prevention. The study found an inverse relationship between knowledge and practice and a relationship between ethnicity and knowledge (p<0.05), between knowledge and practice (p<0.05). Conclusion: The percentage of students with satisfactory knowledge and practice is low. Health education and communication activities need to be promoted to enhance students’ self-awareness and responsibility in preventing dengue fever.